Hydrophobization of Monolithic Resorcinol-Formaldehyde Xerogels by Means of Silylation - Fabian Henn; René Tannert (Gels, 2022)
In materials research, the control of wettability is important for many applications. Since they are typically based on phenolics, organic aerogels, and xerogels are intrinsically hydrophilic in nature, and examples of the chemical functionalization of such gels are scarce and often limited to powders. This study reports on the silylation of monolithic resorcinol-formaldehyde (RF) xerogels using solutions of silyl chlorides and triflates, respectively, in combination with an amine base. The resulting gels are structurally characterized by means of elemental analysis, X-ray photoelectron spectroscopy, pycnometry, sorption analysis, and scanning electron microscopy with electron-dispersive X-ray spectroscopy. The wetting behavior of the silylated gels was studied by the determination of the contact angle to water after exposure of the gels to ambient air. Additionally, the uptake of liquid water and aqueous acids and bases was investigated. As a result, processes for the functionalization of RF xerogels with sterically demanding silyl moieties have been established. Although the analyses indicate that silylation occurred to a rather small extent, highly hydrophobic gels resulted which retained the wetting behavior over the course of several months with contact angles of >130°. Monoliths bearing sterically demanding silyl groups showed higher stability towards aqueous acid than trimethylsilylated RF gels.